--- a/src/HOL/Induct/Term.thy Sat Jun 20 16:08:47 2015 +0200
+++ b/src/HOL/Induct/Term.thy Sat Jun 20 16:23:56 2015 +0200
@@ -15,8 +15,8 @@
text \<open>\medskip Substitution function on terms\<close>
-primrec subst_term :: "('a => ('a, 'b) term) => ('a, 'b) term => ('a, 'b) term"
- and subst_term_list :: "('a => ('a, 'b) term) => ('a, 'b) term list => ('a, 'b) term list"
+primrec subst_term :: "('a \<Rightarrow> ('a, 'b) term) \<Rightarrow> ('a, 'b) term \<Rightarrow> ('a, 'b) term"
+ and subst_term_list :: "('a \<Rightarrow> ('a, 'b) term) \<Rightarrow> ('a, 'b) term list \<Rightarrow> ('a, 'b) term list"
where
"subst_term f (Var a) = f a"
| "subst_term f (App b ts) = App b (subst_term_list f ts)"
@@ -37,8 +37,8 @@
text \<open>\medskip Alternative induction rule\<close>
lemma
- assumes var: "!!v. P (Var v)"
- and app: "!!f ts. (\<forall>t \<in> set ts. P t) ==> P (App f ts)"
+ assumes var: "\<And>v. P (Var v)"
+ and app: "\<And>f ts. (\<forall>t \<in> set ts. P t) \<Longrightarrow> P (App f ts)"
shows term_induct2: "P t"
and "\<forall>t \<in> set ts. P t"
apply (induct t and ts rule: subst_term.induct subst_term_list.induct)